Teachers’ experiences implementing deep learning to improve EFL writing - Yemima Pitaloka Bronte Anwar; Diva Maulida; Dianita Aristiani; Lilia Indriani (Metathesis: Journal of English Language, Literature, and Teaching, 2026)
In the 21st century, critical thinking and digital literacy have become essential in education. However, despite the Merdeka Curriculum’s goal to promote creativity and autonomy, writing instruction often remains focused on grammar, resulting in low student engagement and writing anxiety. This study aims to examine how deep learning strategies, based on mindful, meaningful, and joyful learning, enhance students’ writing skills and engagement. Using a qualitative narrative inquiry design, the study explores the experiences of a pre-service teacher and her students. Data were collected through observation, interviews, and documentation. The findings show that deep learning strategies improve students’ engagement, confidence, and idea development in writing. Mindful learning promotes metacognitive awareness, meaningful learning helps students connect ideas to personal experiences, and joyful learning reduces anxiety and increases motivation. The use of Virtual Reality (VR) further supports students’ imagination and participation. These findings imply that integrating deep learning strategies with supportive learning environments and appropriate technology can effectively improve students’ writing development and should be considered in teaching practices within the Merdeka Curriculum.